Morphological Indices of Drought Tolerant of Some Paddy Varieties (Oryza sativa L.) In West Sumatera Using Standard Evaluation System (SES) For Rice - syauli mardita; Violita Violita (UNIVERSITAS NEGERI PADANG, 2019)
Rice is an important food crop that consumed by more than half of the world's population, but almost every year there is decrease rice production in field, this is due availability of land and water as main source of agriculture. Therefore optimization of dry land as agricultural is needed, but many things are of concern to dry land, especially water sources are minimal. Therefore, it is need have rice seeds are suitable and adaptive to dry land, the response of rice plants to drought can observed from physiological, morphological and anatomical changes. This research was conducted in August to December 2018 in research laboratories, wire houses and plant physiology laboratories, Faculty of Mathematics and Natural Sciences, Padang State University. This study was to obtain a drought tolerant morphological index from several paddy seeds in West Sumatera, so indexes showed that rice seeds were tolerant to drought by observing morphological changes, namely leaf rolling (DPD), shoot top index (IKP). ), and plant recorvry (TP) using the SES (Standard Evaluation System) method for rice. Data is processed using cluster analysis with hierarchical analysis methods. The results showed the most resistant varieties to drought stress were’s Baroto, Situ Bagendit, Randah Kuniang, and Harum.